A comparison of maternal and perinatal outcomes with vaginal delivery: indicated induction versus spontaneous labor. (19th May 2022) - Whittington, Julie R.; Ounpraseuth, Songthip T.; Magann, Everett F.; Wendel, Paul J.; Newton, Lisa; Morrison, John C.
Abstract: Objective: To determine if there is a difference in the maternal and perinatal characteristics and outcomes of women undergoing a medically indicated labor induction and delivering vaginally compared to women in spontaneous labor delivering vaginally. Methods: This is a planned secondary analysis of previously published data with additional data collected for a case-control design. Maternal and perinatal characteristics and outcomes of women undergoing a medically indicated labor induction of labor and delivering vaginally were compared with the next woman who went into labor spontaneously and delivered vaginally. Results: There were 1097 women in the medically indicated labor group and 1096 women in the spontaneous labor group. The medically indicated induction group was younger ( p  < .0001), had less women of "other" race ( p  = .004), were of a lower gravidity and parity ( p  < .0001), had a lower Bishops' score on admission ( p  < .0001), had a greater proportion of umbilical arterial cord pH values <7.1 and <7.0 ( p  < .0001). Additionally, the induction group had longer first and second stages of labor ( p  < .0001). While the unadjusted rates of post-partum complications and NICU admission were higher in the medically indicated labor induction group, only cord gas pH <7.1 remained statistically significant after adjustment. Conclusion: Even with successful vaginal delivery of a medically indicated induction of labor, the risk for adverse outcomes remains elevated.